Determinação das alterações de nutrientes e respostas do fitoplâncton a um evento de dragagem em um porto de macromarés na margem equatorial brasileira - ARAÚJO, Bethânia de Oliveira (2018)
Dredging is a necessary port activity for the deployment and maintenance of navigation channels. However, it is common for this activity to increase the turbidity, thus reducing the luminosity and, consequently, the phytoplankton productivity. The port complex of São Marcos Bay is the second largest port complex in Latin America, located in an area with a macrotidal regime. The objective of this work was to evaluate the effects of dredging in four stages (pre-dredging, dredging I, dredging II, and post-dredging) on the phytoplankton community (biomass and abundance of phytoplankton) and environmental variables at seven fixed points. Subsequently, one-way ANOVA, the Pearson correlation, Principal Component Analysis and Canonical Correspondence Analysis were applied for statistical analysis. The biomass concentrations (chlorophyll a) declined from the pre- to post-dredging stage (15.75– 4.56 mg m-3 ). The phytoplankton abundance was significantly lower in dredging stage I (22,003 cells L-1 ) and dredging stage II (36,443 cells L-1 ), due to the lower availability of nitrogen and phosphate compounds and iron and manganese metals caused by the increase of turbidity. Dredging stage I showed the lowest diversity and richness. The species Coscinodiscus radiatus and Cyclotella and Nitzschia complexes showed a strong correlation with abundance because they were influenced by turbidity and concentrations of total manganese, silicate and ammonium ion. Despite the drastic reduction in abundance values during dredging stages I and II, the phytoplankton community reestablishes itself in the postdredging stage.